2022
DOI: 10.5194/acp-22-12705-2022
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar COVID-19 effects in the Greater Tokyo Area revealed by spatiotemporal variabilities of tropospheric gases and light-absorbing aerosols

Abstract: Abstract. This study investigated the spatiotemporal variabilities in nitrogen dioxide (NO2), formaldehyde (HCHO), ozone (O3), and light-absorbing aerosols within the Greater Tokyo Area, Japan, which is the most populous metropolitan area in the world. The analysis is based on total tropospheric column, partial tropospheric column (within the boundary layer), and in situ observations retrieved from multiple platforms as well as additional information obtained from reanalysis and box model simulations. This stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 81 publications
1
3
0
Order By: Relevance
“…Several epidemiological studies have shown that nitrogen dioxide (NO 2 ) exposure is often associated with adverse health effects such as lung cancer, asthma, and cardiopulmonary mortality ( Wang et al, 2020 ; Berg et al, 2021 ). Based on the average of in-situ observational data at air pollution network stations in Tokyo metropolis, during the lockdown from April–May 2020, NO 2 experienced a decrease of 15.30% compared to the previous year, similar to other studies from satellite data found for Tokyo a value of 19% decrease ( Ghahremanloo et al, 2021 ; Damiani et al, 2022 ).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Several epidemiological studies have shown that nitrogen dioxide (NO 2 ) exposure is often associated with adverse health effects such as lung cancer, asthma, and cardiopulmonary mortality ( Wang et al, 2020 ; Berg et al, 2021 ). Based on the average of in-situ observational data at air pollution network stations in Tokyo metropolis, during the lockdown from April–May 2020, NO 2 experienced a decrease of 15.30% compared to the previous year, similar to other studies from satellite data found for Tokyo a value of 19% decrease ( Ghahremanloo et al, 2021 ; Damiani et al, 2022 ).…”
Section: Resultssupporting
confidence: 80%
“…In Greater Tokyo Area, the change in people's mobility was smaller and more gradual compared to other worldwide countries because of avoidance of adopted strict legal restrictions, showing the largest mobility drop during the weekends, with decreases about 10% larger than on weekdays. ( Sugawara et al, 2021 ; Damiani et al, 2022 ). However, the implemented COVID-19 pandemic lockdowns during States of Emergency (SOEs) in Tokyo ( Table 1 ) led to a sharp drop in socio-economic activities, including reductions in fossil fuel use, industry productions, and traffic volumes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PANs did not show marked changes over São Paulo or Tokyo despite major NO x perturbations. O 3 over Tokyo also did not significantly change with COVID‐19 lockdown measures; this has been attributed to a shift in the underlying photochemical regime from VOC‐limited toward the transition zone where O 3 production is expected to be equally sensitive to changes in both NO x and VOCs (Damiani et al., 2022; Ito et al., 2021; Q. Wang & Li, 2021). São Paulo experienced an increase in O 3 in April and May, but largely in areas most seriously impacted by vehicle emissions (Alvim et al., 2023).…”
Section: Resultsmentioning
confidence: 99%